THE DETERMINATION OF BEGINNING OF PASAH ANDTELLASAN AT AL-KARAWI ISLAMIC BOARDING SCHOOL OF SUMENEP REGENCY - Fathor Rausi (Al-Hilal: Journal of Islamic Astronomy, 2020)
The determination of beginning of Pasah and Tellasan in Al-Karawi Islamic Boarding Schools is often different from the decisions of the government (Ministry of Religion of the Republic of Indonesia) or Islamic society organizations, such as Nahdlatul Ulama or Muhammadiyah. Al-Karawi Islamic Boarding School uses the calculating method compiled by one of the boarding school educators in determining the beginning of fasting and Eid. This research is intended to analyze the phenomenon of early fasting and Eid froma sociological perspective. These problems are discussed with field research through the socio legal studies approach. The results of this study indicate that the beginning determination of fasting and Eid Al-Karawi Islamic Boarding School is often different from the government is due to the strong patronage relationship among kiai, santri and the residents of Karawi village.